Social and Religious Dynamics: Study of the Nyuguh Tradition in Pasir Gaok Village Indonesia - Janur Ramadhina; Muhamad Ridwan Effendi (Universitas Negeri Jakarta, 2024)
Tradition is something that has been passed down from generation to generation by a group of people and is difficult to abandon. Indonesia is a country with various tribes, races and religions, so it has various traditions within it. One form of tradition that exists in society is a procession honoring the spirits of deceased ancestors. In Pasir Gaok Village, this procession or tradition is called the Nyuguh Tradition. This research aims to find out the processions and meanings contained in the Nyuguh tradition in Pasir Gaok Village and what implications are obtained from this tradition. The method used is a qualitative method in which data collection is carried out by means of interviews, observation and literature study. The results of this research show that the Nyuguh tradition is carried out by several communities in Pasir Gaok Village who are still strong in their culture. This tradition has implications for vertical relationships (relationships to God) and horizontal relationships (relationships between humans or social groups) in the people of Pasir Gaok Village Indonesia